1999
DOI: 10.1021/bi991470c
|View full text |Cite
|
Sign up to set email alerts
|

The sen1+ Gene of Schizosaccharomyces pombe, a Homologue of Budding Yeast SEN1, Encodes an RNA and DNA Helicase

Abstract: Two polynucleotide-dependent ATPases, 95 and 181 kDa in size, have been purified to near homogeneity from cell-free extracts of Schizosaccharomyces pombe. Despite their size differences, their biochemical properties were strikingly similar. Both enzymes were capable of unwinding RNA and DNA duplexes in keeping with their ability to hydrolyze ATP in the presence of either ribo- or deoxyribopolynucleotide. In addition, they were capable of unwinding DNA/RNA or RNA/DNA hybrid duplexes and translocated in the 5' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 48 publications
(88 reference statements)
4
86
0
Order By: Relevance
“…Consistent with the reported activity of native Sen1 purified from S. pombe (18), S. cerevisiae Sen1-HD has 5Ј-to 3Ј-helicase activity (Fig. 4).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with the reported activity of native Sen1 purified from S. pombe (18), S. cerevisiae Sen1-HD has 5Ј-to 3Ј-helicase activity (Fig. 4).…”
Section: Discussionsupporting
confidence: 89%
“…Previously, a 5Ј-to 3Ј-RNA and DNA helicase activity purified from Schizosaccharomyces pombe cell extract was attributed to an ortholog of S. cerevisiae Sen1 (18). More recently, however, TAP-tagged Sen1 purified from S. cerevisiae exhibited no DNA/RNA duplex unwinding activity and did not stably bind RNA, despite having DNA-and RNA-dependent ATPase activity (19).…”
mentioning
confidence: 99%
“…In addition to establishing that HCoV p66 HEL is an SF1 RNA helicase, we have shown that it differs significantly from the previously characterized SF2 RNA virus helicases+ Thus, although all RNA virus helicases investigated so far operate in 39-to-59 direction (reviewed in Kadaré & Haenni, 1997), the coronavirus RNA duplex-unwinding activity has 59-to-39 polarity+ This finding implies that the coronavirus helicase binds to the 59 single-stranded region of a partial-duplex RNA and unwinds this duplex in a 59-to-39 direction with respect to the RNA strand used for entry+ In this context, it will be important to find out whether the difference in the polarity of the unwinding process between the coronavirus helicase and RNA viral SF2 helicases also reflects a fundamental difference between SF1 and SF2 helicases, that is, do other RNA viral SF1 helicases share the 59-to-39 polarity with the coronavirus helicase+ The only other RNA viral SF1 helicase activity reported so far, that of the Semliki Forest virus nsp2 protein, showed extremely low duplex-unwinding activity in vitro and, to our knowledge, has not yet been characterized with regard to its polarity (Gomez de Cedrón et al+, 1999)+ Studies on molecular motors of the kinesin superfamily (Henningsen & Schliwa, 1997) have demonstrated that the specific arrangement of motor domains with their associated accessory domains may determine the polarity of translocation+ It is therefore con- ceivable that the directionality of helicases may also be controlled by additional domains rather than by the intrinsic properties of the core helicase itself+ Indeed, numerous cellular helicases carry additional nucleic acid-binding domains, including zinc finger structures (reviewed in Gorbalenya & Koonin, 1993)+ Most of these additional domains are either attached to one or the other of the core helicase termini, or they are inserted between the helicase motifs Ia and II or IV and V, respectively (Gorbalenya & Koonin, 1993;Bird et al+, 1998)+ Obviously, it will be interesting to examine if the amino terminal zinc finger contributes to the function of the coronavirus helicase+ Furthermore, the possibility that there are additional contacts between the HCoV enzyme and the duplex region of the substrate needs to be investigated+ Such interactions have recently been postulated to be of critical importance for the duplexunwinding activity of the bacterial DNA helicase PcrA (Velankar et al+, 1999)+ Another important finding of this study is the apparent lack of specificity of the coronavirus helicase for RNA versus DNA substrates+ The vast majority of helicases act in a very specific manner on either RNA or DNA+ The few enzymes that lack this specificity (Stahl et al+, 1986;Scheffner et al+, 1989;Zhang & Grosse, 1994;Bayliss & Smith, 1996;Gwack et al+, 1997;Laxton et al+, 1998;Costa et al+, 1999;Kim et al+, 1999) are mainly virus encoded or so-called noncanonical helicases+ Structural data on one of these enzymes, HCV NS3, have recently shown that the primary interactions between NS3 and the single-stranded substra...…”
Section: Biochemical Properties Of the Hcov Helicasementioning
confidence: 80%
“…1e), and so we named it senataxin (SETX). Saccharomyces cerevisiae Sen1p is involved in splicing and termination of tRNA, small nuclear RNA and small nucleolar RNA and has RNA helicase activity encoded by its C-terminal domain [7][8][9] . Schizosaccharomyces pombe has two Sen1 genes.…”
mentioning
confidence: 99%
“…Schizosaccharomyces pombe has two Sen1 genes. The first reported S. pombe Sen1p (Sen1p1, encoded on chromosome I) has both RNA and DNA helicase activities 9 . Of all the fungal Sen1p proteins, however, the second S. pombe Sen1p (Sen1p2, encoded on chromosome II) has the highest homology with senataxin over the N-terminal domain (20% identity over 466 residues).…”
mentioning
confidence: 99%